THE CHALLENGES IN THE SCHOOL INCLUSION OF STUDENTS WITH SPECIAL NEEDS IN EARLY CHILDHOOD EDUCATION - Rodrigues Maia, Felipe (Revista Gênero e Interdisciplinaridade, 2026)
The school inclusion of students with special needs in early childhood education is a central topic in contemporary education, as it lays the foundation for children’s cognitive, social, and emotional development. Despite legal guarantees in Brazil, the effective implementation of inclusion faces pedagogical, structural, and social challenges. This article aims to analyze the main obstacles faced in the inclusion of children with special needs in early childhood education, considering the perspectives of teachers, schools, and families. This is a qualitative research of a bibliographic nature, based on a review of national and international literature. The results indicate that the lack of specific teacher training, the scarcity of adapted educational resources, physical barriers, and difficulty in family engagement are the main challenges. It is concluded that effective inclusion in early childhood education depends on consistent public policies, teacher training, school adaptation, and active family participation.